Assessment of the Phase Synchronization Effect in Modal Testing During Operation - Ong, Zhi Chao; Lim, Hong Cheet; Khoo, Shin Yee; Ismail, Zubaidah; Kong, Keen Kuan; Abdul Ghaffar, Abdul Rahman (Zhejiang University Press, 2017)
The impact-synchronous modal analysis (ISMA), which uses impact-synchronous time averaging (ISTA), allows modal testing to be performed during operation. ISTA is effective in filtering out the non-synchronous cyclic load component, its harmonics, and noises. However, it was found that at operating speeds that coincide with the natural modes, ISMA would require a high number of impacts to determine the dynamic characteristics of the system. This finding has subsequently reduced the effectiveness and practicality of ISMA. Preservation of signatures during ISTA depends on the consistency of their phase angles on every time block but not necessarily on their frequencies. Thus, the effect of phase angles with respect to impact is seen to be a very important parameter when performing ISMA on structures with dominant periodic responses due to cyclic load and ambient excitation. The responses from unaccounted forces that contain even the same frequency as that contained in the response due to impact are diminished with the least number of impacts when the phase of the periodic responses is not consistent with the impact signature for every impact applied. The assessment showed that a small number of averages are sufficient to eliminate the non-synchronous components with 98.48% improvement on simulation and 95.22% improvement on experimental modal testing when the phase angles with respect to impact are not consistent for every impact applied.